PENGARUH PENERAPAN GREEN ACCOUNTING MELALUI PROFITABILITAS SEBAGAI VARIABEL MEDIASI TERHADAP NILAI PERUSAHAAN - Ekawati, Ardini Sevilla (Media Akuntansi dan Perpajakan Indonesia, 2023)
The purpose of this research is to determine whether profitability is able to mediate the effect of implementing Green Accounting on firm value in manufacturing companies in the consumer non-cyclicals sector which are listed on the Indonesia Stock Exchange in 2019–2021. Panel data model with path analysis is used to perform data processing in this study. The results of statistical data processing on 117 observation samples from 30 companies show that Green Accounting has no effect on firm value. However, green accounting variables have a significant negative effect on profitability, and profitability has a positive effect on firm value. The sobel test value also indicates that profitability is still not able to mediate the effect of Green Accounting on firm value because when a company’s financial performance decreases, it may be caused by the environmental cost to help the company realize good environmental performance which ultimately makes the company’s value still relatively good.